Pengaruh Limbah Polimer PET dan EVA sebagai Subtitusi Pasir Silika dan Semen terhadap Peningkatan Kuat Lentur, Sifat Fisis dan Karakterisasi Mortar Polimer - Amin, Muhammad; Laksmidevi Juwono, Ariadne; Sudibyo, Sudibyo; Suprihatin, Suprihatin; Putriana, Silvia (Jurnal Teknik Sipil, 2024)
Abstract A study was conducted on the manufacture of polymer mortar using Polyethylene Terephthalate (PET) as a substitute for sand with a composition of 0%, 0.2%, 0.5%, 0.8%, 1.1%, 1.4% and Ethylene Vinyl Acetate (EVA) polymer composition of 0%, 2%, 4%, 6%, 8%, 10%. Sand, cement and polymer materials were weighed and molded into a size of 16 × 4 × 4 cm3 and soaked in water for 7 and 14 days. The highest flexural strength value obtained at 14 days of immersion was 6.50 MPa, porosity at 7 days of 12.20%, absorption value at 7 days of 6.65% and density at 14 days of 1.89 g/cm3 with a polymer substitution composition for sand of 10% EVA polymer: 1.4% PET. Characterization of the sample was carried out using X-ray Diffraction (XRD), X-ray fluorescence (XRF), Scanning Electron Microscope- Energy Dispersive X-ray spectroscopy (SEM-EDS), and Fourier-transform infrared spectroscopy (FTIR). XRF characterization obtained CaO of 46.95% and SiO2 of 24.45%, which is the result of CS-H formation. XRD characterization obtained calcite, quartz, corundum, hematite phases. SEM-EDS images show a cauliflower-like morphology and dominant elements of Ca and Si. FTIR functional groups are O-H, C=O, C-C, C-H, Si-O-Si, and Si-O is a portlandite group. The increasing addition of EVA and PET polymers results in high porosity and high flexural strength. Keywords: Polymer, mortar, EVA, PET, and characterization.